Exploring entropy landscapes using hard particle Monte Carlo metadynamics - Charlotte Shiqi Zhao; Sun-Ting Tsai; Sharon C. Glotzer (Proceedings of the National Academy of Sciences, 2026)
For more than two decades, metadynamics has been a powerful tool for improving the sampling of rare events and metastable states in molecular systems. It has been sparingly used, however, to study the crystallization of colloidal systems, especially those comprised of hard particles with anisotropic shapes. In this work, we propose a method, hard particle Monte Carlo metadynamics (HPMC-MetaD), that combines the HPMC-scheme with metadynamics, thereby extending the application of metadynamics to hard particle systems whose phase transitions are driven solely by entropy. As illustrative examples, we use HPMC-MetaD to study five shapes previously reported to be candidate glass formers because of their stubbornness to crystallization. With HPMC-MetaD, we observe crystallization for all five shapes and construct entropy landscapes. These results demonstrate the effectiveness of HPMC-MetaD as a tool for exploring self-assembly in hard particle systems, which will enable a more comprehensive understanding of the underlying mechanisms, ultimately allowing predictive control over the assembly pathways.